Digital Storytelling as a Pedagogical Strategy and Literary Analysis: A Systematic Literature Review - Aldian Yusup (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2026)
The development of digital technology has brought significant changes in the world of education, including in language learning and literary studies. One of the innovations that stands out is digital storytelling, which is the practice of storytelling by utilizing digital media to present a more interactive and contextual narrative. This research departs from the urgency of the need for English learning methods that are adaptive to the digital generation as well as relevant to the phenomenon of fragmented self in contemporary literature. The purpose of the research is to systematically review the literature related to digital storytelling and fragmented self with a focus on pedagogical contributions and theoretical implications in literary studies. The method used is Systematic Literature Review (SLR) with the PRISMA 2020 flow. The selection process was carried out through the Scopus database with the keywords "Digital Storytelling", "English", and "Fragmented Self" in the range of 2015–2025. Of the initial 98 articles, only 4 met the inclusion criteria and were further analyzed. The results of the study show that digital storytelling is effective in increasing students' motivation, positive attitudes, and English skills. In addition, this method plays a role in the formation of identity and self-expression, especially in multicultural contexts such as refugee children. In the realm of literature, digital storytelling is relevant to understand the representation of the fragmented self as a phenomenon of divided identity in the digital era. Overall, digital storytelling proved to be not only a pedagogical strategy, but also a cross-disciplinary academic instrument that enriched the study of contemporary education and literature.